Comparing forest structures in the border areas of the demilitarized zone of South Korea. Issue 1 (2nd January 2017) - Seo, Yeongwan; Lee, Daesung; Cha, Dusong; Choi, Jungkee
ABSTRACT: This study was conducted to inventory forest structures focusing on the border areas of the demilitarized zone, which are Goseong, Inje, Yanggu, Hwacheon, Cheolwon, Yeoncheon, and Paju, in South Korea. A total of 707 points were inventoried using a point sampling method. Forest type, tree species, diameter at breast height (DBH), and stand volume per hectare were analyzed and compared. The broad-leaved had the highest frequency with an average of 88%, followed by mixed (7%) and coniferous (5%) forest types in the border areas. A total of 62 tree species were observed and Quercus mongolica had the highest frequency with an average of 28%. By DBH class, small had the highest percentage with 63%, medium was 30%, and large was 7%. Mean DBH was relatively low (16.1 cm) with a range of 13.2 cm to 20.3 cm and the mean stand volume was 107 m 3 ha −1 with a range of 80 m 3 ha −1 to 123 m 3 ha −1 . Compared to the stand volume (137 m 3 ha −1 in average) of the administrative district of the Korea Forest Service, our results showed that the stand volume of the border area is relatively low.